2022
DOI: 10.1038/s41598-022-18221-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal proteomics study of serum changes after allogeneic HSCT reveals potential markers of metabolic complications related to aGvHD

Abstract: Even though hematopoietic stem cell transplantation (HSCT) allows successful treatment for many malignant and non-malignant disorders, its curative potential remains limited by severe side effects, including infections and other transplant-related complications such as graft-versus-host disease (GvHD). This study examined changes in serum proteome via high-performance two-dimensional gel electrophoresis (2-DE) during HSCT to search for diagnostic biomarkers for post-HSCT complications. Longitudinal proteomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Pretreatment of serum for the removal of major proteins that would otherwise impede the analysis of minor proteins in 2DE was performed following previously described methods 24 , 25 . Briefly, 60 µL of serum was mixed with 180 µL of dilution buffer (Seppro IgY 14 protein kit, Sigma-Aldrich Co., St. Louis, MO, US) and filtered through a Spin-X Column (0.45 µm, Corning, New York, U.S.) at 10,000 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pretreatment of serum for the removal of major proteins that would otherwise impede the analysis of minor proteins in 2DE was performed following previously described methods 24 , 25 . Briefly, 60 µL of serum was mixed with 180 µL of dilution buffer (Seppro IgY 14 protein kit, Sigma-Aldrich Co., St. Louis, MO, US) and filtered through a Spin-X Column (0.45 µm, Corning, New York, U.S.) at 10,000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…The 2DE experiment was conducted following previously reported methods 24 , 25 . Briefly, the DeStreak Rehydration Solution containing 50 µg of proteins was absorbed into Immobiline DryStrips (7 cm, pH 3–10, Cytiva, MA, US) for 18 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S.Y. Wong et al (2022) found in their research that the use of red blood cells reduces the number of microaggregates, the absence of plasma coagulation factors and a significant number of platelets, and reduces the risk of contracting vector-borne infections.…”
Section: Resultsmentioning
confidence: 99%
“…S.Y. Wong et al (2022) note that transfusion of blood and its components is effective in animals with anaemia of various genesis (post-haemorrhagic, haemolytic, aplastic). B.…”
Section: Literature Reviewmentioning
confidence: 99%